Corrective feedback – its role and impact in enhancing learners’ language performance / Fazmawati Zakaria and Surina Nayan - Zakaria, Fazmawati; Nayan, Surina (UiTM Cawangan Kedah, 2022)
Coronavirus pandemic has affected teaching and learning scenario in education institutions. The learning motivation of learners is affected by this crisis. One of ways that educators can do to help these learners is to provide support in terms of feedback. Feedback is important in language learning and teaching because not only it can increase learners’ motivation but also influence learners’ language performance. Debate about the role and the impact of corrective feedback on learners’ language learning has been prominent in recent years. Numerous research were conducted to investigate whether corrective feedback facilitates their language learning performance. As educators, we need to recognize the value of effective feedback to both the learners and educators. In this paper, concepts, characteristics and importance of effective corrective feedback in relation to motivation are discussed on theoretical and practical grounds. Furthermore, this paper also discussed reviews of supporting research evidence which indicate the influence of corrective feedback on learners’ language performance. Lastly, recommendations for educators to explore ways to improve their feedback techniques in order to maximize learners’ achievement in language learning are also suggested.